2017
DOI: 10.1098/rsfs.2016.0080
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and flight control of a flapping-wing robotic insect in the presence of wind gusts

Abstract: With the goal of operating a biologically inspired robot autonomously outside of laboratory conditions, in this paper, we simulated wind disturbances in a laboratory setting and investigated the effects of gusts on the flight dynamics of a millimetre-scale flapping-wing robot. Simplified models describing the disturbance effects on the robot's dynamics are proposed, together with two disturbance rejection schemes capable of estimating and compensating for the disturbances. The proposed methods are experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…It thus represents a trade-off between clearance and aerodynamic effectiveness. To determine how effectively insect-inspired flapping wings might negate lateral wind, Chirarattananon et al [16] developed a new flight controller with disturbance rejection schemes capable of estimating and stabilizing the robot's position with respect to the ground in 0.8 ms 21 lateral wind. The effectiveness of such flapping wings can be improved by aeroelastic tailoring and morphing them throughout the wingbeat like a bat.…”
Section: Aerial Robotics Advancesmentioning
confidence: 99%
“…It thus represents a trade-off between clearance and aerodynamic effectiveness. To determine how effectively insect-inspired flapping wings might negate lateral wind, Chirarattananon et al [16] developed a new flight controller with disturbance rejection schemes capable of estimating and stabilizing the robot's position with respect to the ground in 0.8 ms 21 lateral wind. The effectiveness of such flapping wings can be improved by aeroelastic tailoring and morphing them throughout the wingbeat like a bat.…”
Section: Aerial Robotics Advancesmentioning
confidence: 99%
“…Frontal and lateral inflows contributed to increase lift, whereas drag was found to be linearly proportional to flow speed [9,12,13]. While Chirarattananon et al [14] experimentally showed that the effects of frontal inflows were more pronounced compared with oriented laterally, Jones & Yamaleev [9] revealed that flapping wings can alleviate the effect of moderate or even strong frontal inflows whose mean velocity is comparable with the wing tip velocity. In addition, their numerical results revealed that the mean lift tended to increase when the wing oriented towards the lateral inflow, whereas it decreased when the wing was oriented away from the lateral inflow.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, multirotors are not energy efficient platforms for long distance/endurance operations, since most of the energy is devoted to lifting their own weight, whereas a fixed or flapping wing vehicle takes advantage of the aerodynamic lift forces generated during forward flight [14,15]. The possibility to glide as birds do [16,17], exploiting the potential energy and the wind gusts [18], extends the flying ability and reduces the potential damages due to crashes or impacts in case of failure. On the other hand, and related to this last point, multirotors are not suitable platforms for close interaction with humans, in terms of safety, due to the propellers [19], whereas the damage that a flapping wing vehicle may cause is relatively low.…”
Section: Introductionmentioning
confidence: 99%